LIBRARIES DURING THE RULE OF THE SHAIBANIKHAN’S - Soibnazar Davlatov (Scholars Digest Publishing, 2023)
In this article, information about the library in Shaibanikhan’s palace during his reign, where both his own works and the collections made with his participation are stored in some libraries, it was said that manuscripts were carefully kept in Shaibanikhan’s madrasa in Samarkand among which there were quite a few rare manuscripts.
Keywords: library, book, manuscripts, madrada, mosque, culture, science, art, even, bookbinder.